The discovery and development of the Namaqualand Diamond Field, 1925-1950 - De La Harpe, Anthony (Department of Historical Studies, 2025)
Drawing on archival sources, secondary published materials and interviews, this thesis is a historical study of diamond mining in Namaqualand, Northern Cape Province of South Africa, during the period 1925 to 1950. It is a history that led to the region becoming synonymous with diamonds. The focus then is the first diamond find on the coast near Port Nolloth, as well as subsequent mining operations at Alexander Bay (the first State mining venture which contained some socialist elements) and Kleinzee (an extension of the De Beers Consolidated Mines empire). Captain Jack Carstens, ex-soldier and amateur prospector, is generally credited with having discovered the first stone in Namaqualand. However, vague rumours that there were earlier finds in the interior of Namaqualand can now be confirmed. The role of the major players – the State, the mining companies and the workers – is central to this study. Diamond mining has indeed had (and continues to have) a major impact on the local economy and society. By 1925 the harsh socio-economic conditions resulting from closure of the copper mines in Namaqualand, were compounded by drought, unemployment and widespread poverty. Against this background came the fortuitous discovery of the first precious stones on Port Nolloth Reserve or Commonage. This was followed by the astounding discoveries on the coastal terraces at Alexander Bay and Kleinzee, which quickly outdistanced the importance of the copper industry founded in Namaqualand in 1852. This thesis also throws light on the historical relations between the mining companies and their workers who were recruited from the local communities and elsewhere. The discovery of diamonds brought with it migrant labour housed in single-sex hostels or compounds, as well as the entrenchment of wage labour. What originated as a response by labour to economic circumstances would, in time, become entrenched in policy in the interest of the mining houses. Attention is furthermore drawn to the external political and economic forces that during the mid-twentieth century shaped the dominion of the companies over the people on and around the mines. In this way, the wider history of inequitable relations between a white-controlled state and white capitalists on the one hand, and on the other, the local people dispossessed of their historic rights to land and a fair share of the mineral wealth of the district, is illuminated. The labour force was, in addition, racialized along lines of race, ethnicity and class specifically in regard to the preferred status of “poor whites” in the mining industry. In short, the thesis examines how the history of mining sustained the racial hierarchies of colonialism, segregation and apartheid, and the marginalisation of non-white labour. Today, the diamond diggings on the Alexander Bay coast and the closed down mines of Kleinzee along the lower Buffels have simply emphasised the fact that Namaqualand's wealth and potential lie beneath the ground. Unrehabilitated mining sites and huge mine dumps bear witness to a century of diamond mining which left local communities uncertain and having little to show. The future, however, points in the direction of undersea diamond reserves off the coast. Marine mining will certainly continue to grow in importance as the onshore deposits are depleted, opening a new chapter of mining history.